Earthquake Distributions in Sulaimaniyah, North of Iraq (Iraqi National Journal of Earth Science (INJES), 2026)
One of the main natural threats is earthquakes, which pose a serious threat to human life and property. To examine seismic activity in Sulaymaniyah, a city, statistically determined distributions of earthquake hypocenters, magnitudes, and epicenters were reviewed from 1900 to 2018. Three contour maps that indicate the distribution of earthquakes in the study region were created using the Intercontinental Seismological Center Bulletin. The spreading of earthquakes shows that there is an increase in the number of earthquakes and their magnitude in areas with active faults, specifically in the southeastern and northwestern parts of the city of Sulaymaniyah, at the collision ridges between the Arabian and Iranian plates, and a decrease in the intensity, number of earthquakes, and their seismic magnitude in the center of the city itself. This means that Sulaymaniyah is the most seismically active and dangerous region in northern Iraq because it is located along the Zagros-Taurus belt, which is one of the most active seismic belts.
Keywords: Sulaymaniyah, Active Fault, Magnitude, Tectonic, Zagros